The variability of application execution times on a multi-core platform - Nelis, Vincent (2017)
16th International Workshop on Worst-Case Execution Time Analysis (WCET 2016). 5, Jul, 2016. Toulouse, France.WCET was held as part of ECRTS 2016 that took place in Toulouse, France on July 5-8, 2016.